2017
DOI: 10.1080/21645515.2017.1321182
|View full text |Cite
|
Sign up to set email alerts
|

“To each his own”: Discussions of vaccine decision-making in top parenting blogs

Abstract: Although social media provides a way for people to congregate with like-minded others, it can also play a role in spreading misinformation about public health interventions. Previous research demonstrates that parents who use the Internet to gather information on vaccination are more likely to hold anti-vaccination beliefs. There has been little examination of vaccination decision-making discussions on parenting blogs. This study seeks to fill that gap. Posts and comments on the top 25 top parenting blogs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 29 publications
0
48
0
4
Order By: Relevance
“…Previous research examining this type of information, concerning vaccines, demonstrated that many blog posts and subsequent comments take an anti-vaccination standpoint although the overall quality of pro-vaccination webpages is superior to anti-vaccination online sources. [54][55][56] There were some potential limitations of the current study that must take into account in the interpretation of the results. Firstly, although the associations between the main explanatory variables and the different outcomes of interest were identified, caution should be taken into account when interpreting the results owing to the cross-sectional study design applied, which limited us from making any conclusion on causal relationship between these factors.…”
Section: Discussionmentioning
confidence: 93%
“…Previous research examining this type of information, concerning vaccines, demonstrated that many blog posts and subsequent comments take an anti-vaccination standpoint although the overall quality of pro-vaccination webpages is superior to anti-vaccination online sources. [54][55][56] There were some potential limitations of the current study that must take into account in the interpretation of the results. Firstly, although the associations between the main explanatory variables and the different outcomes of interest were identified, caution should be taken into account when interpreting the results owing to the cross-sectional study design applied, which limited us from making any conclusion on causal relationship between these factors.…”
Section: Discussionmentioning
confidence: 93%
“…21,23 In contrast to traditional media, content posted need not undergo editorial curation nor scientific vetting, and may represent a more complex mixture of evidence and personal opinion. 24,25 Further, users frequently maintain anonymity, allowing individuals to express their views unadulterated. 26 Social media is also characterized by its potential to reach large audiences and propagate information very rapidly.…”
Section: Social Mediamentioning
confidence: 99%
“…The quality of health information available online pertaining to specific issues (e.g. HIV/AIDS, vaccination, venomous snake bites) has been extensively evaluated (Barker, Charlton, & Holstege, ; Faasse, Chatman, & Martin, ; Kalichman et al, ; Kata, ; Meleo‐Erwin, Basch, MacLean, Scheibner, & Cadorett, ; Seeman, Ing, & Rizo, ), with many studies highlighting gaps in the information provided (Parvizi, Talai, & Parvizi, ). The variability and relative utility of some assessment tools have also been noted (Beaunoyer et al, ; Fahy, Hardikar, Fox, & Mackay, ).…”
Section: Introductionmentioning
confidence: 99%